Integration of Digital Technology in the Learning Process Through Problem-Based Learning Models - Izlan Sentriyo; Nana Sumarna; La Rabani; Wa Ode L. Arisanti (STAI Hubbulwathan Duri, 2023)
Digital technology is what most affects the education system today because of the aspects of effectiveness, efficiency, and attractiveness offered. The research approach used in this study was a quantitative research design. This study explores the integration of digital technology in students through quantitative data and enriches the data with qualitative analysis. The samples of this study were students of the education faculty majoring in elementary education at a university in Halu Oleo who were selected through convenience sampling. The first phase of the research is to conduct a problem-solving-based lecture process and then be given a standard scale and open-ended questions. Then the second phase, students are given a questionnaire given through a Google Form, which is sent along with all the information and an invitation to participate. The results of the study show the provision of digital technology-based learning content, especially in the problem-solving process, should consider quality, meaningful, and user-friendly materials. including spreadsheet applications, graphics processing; multimedia arrangements; mind/concept mapping; digital video processing; online class management, and online publishing; and the main reason for the inability to complete tasks is dominated by unsupported smart devices; inadequate programs or applications (software); inadequate internet connection; and the ability to operate the application is not supported.